O Projeto Troika em Portugal: media, resiliência e vulnerabilidade - Rodrigues, V. (2018)
This paper aims to analyze the extent to which the Troika Project on visual narratives (2014) helped to give voice to stories of vulnerability and resilience in Portugal, empower the Portuguese society for human progress and how it fits into journalism for development. Furthermore, the article seeks to understand how the project is thematically harmonized in the United Nations problems of the post-2015 development agenda. To address these issues, we conducted an exploratory study through structured interviews of three members of this independent collective. We concluded that, as far as development and human progress issues are concerned, the documentary is more likely to encourage reflection than photographs, and that it may contribute to promoting debate to raise awareness. On the other hand, they do not appear to have generated an immediate potential to empower civil society. Therefore, we suggest combining, whenever possible, narratives that associate either documentaries or recorded audio interviews with key players in future journalistic works in this field of journalism for development, as a way to empower society and contribute more effectively to social change.